Socioeconomic and demographic characteristics as sources of social capital: A study of Indonesia - Choirul Okviyanto; Wildan Syafitri (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
Over a decade, the development in Indonesia has achieved a good performance in macroeconomic indicators: stability in the economic growth and declining trend of poverty rate; however, this development tends to ignore the social phenomena in terms of social capital, in which the social capital index decreases dramatically during the past ten years. This paper aims to examine the sources of social capital in Indonesia. Consequently, the policymakers obtain some information to improve the social capital index in Indonesia. The present study utilizes the Indonesian Happiness Measurement Study (SPTK) 2017 covering 72,317 households around Indonesia and involves trust and tolerance, collective action, and group and network dimensions as a proxy of social capital. This study employs Ordinary Least Squares (OLS) analysis and finds that education is essential in predicting social capital. Besides, this study confirms that gender and location significantly affect social capital, where males and rural residents are likely to have higher social capital than females and urban residents in Indonesia. Eventually, based on research findings, this study offers some policy implementation for enhancing the social capital index in Indonesia: expanding the free educational program, encouraging women's participation in the community, and continue the village funds program.JEL Classification: B55; I25; O10